Factors related to the active role of the volunteer in the crawl probable case of diphteriae - Riza Alfina; Muhammad Atoillah Isfandiari (Universitas Airlangga, 2015)
Diphtheria is caused by the bacterium Corynebacterium diphtheriae. Children aged 2-10 years are vulnerable to contracting. The selection of diphtheria probable cases is difficult, so every year there are children who die from diphtheria. Cadres or volunteer play an important role in the field of developing a toddler family. This study aims to analyze the factors related to the active role of cadres in capturing probable diphtheria cases in the Public health center (PHC) of Sidoarjo. This type of research is observational analytic with a cross-sectional design. The population of this study was all cadres in the PHC of Sidoarjo as many as 516 people. Samples were taken by simple random sampling of 103 respondents. Data collection was carried out using a questionnaire. The variables of this study were the active role of cadres in the selection of probable diphtheria cases, internal factors (knowledge, cadre attitudes), and external factors (support of community leaders, support of community health centers, training of health cadres). The data analysis technique was carried out by means of a logistic regression test. The results showed that 75% of cadres in the PHC of Sidoarjo's working area were active in capturing probable diphtheria cases. Statistical test results show that internal factors that influence the active role of cadres are attitude (p = 0.024), while external factors are support from community leaders (p = 0.022), PHC's support (p = 0.042), and cadre training (p = 0.041). It is expected that cooperation between cadres, community leaders, health center officials, in supporting efforts to increase the ability and activeness of cadres in helping in the field of public health services.